A Taxon Gross Assets of Enterprises as a Form of Presumptive Taxation - Sadka, Efraim (IMF Working Papers; Working Paper ;, 1992)
A tax on gross assets has been introduced in some developing countries where several factors (most notably, high inflation) enabled apparently viable enterprises to report losses for income tax purposes. The idea of a tax on the value of assets, rather than on the income that the assets generate, seems to have originated in the 17th century in Milan. It was more recently advocated by Luigi Einaudi and Maurice Allais, but their contributions have remained unknown in the Anglo-Saxon world. The economic implications of such a tax are analyzed in this paper. Special attention is devoted to efficiency and administrative aspects. Practical considerations suggest that the tax on gross assets serves as a minimum income tax rather than as a final tax.